Incorporating Local Wisdom Into the Consumer Protection Legal Regime: A Comparison Between Indonesia And Australia - Widiatedja, I Gusti Ngurah Parikesit (Udayana Journal of Law and Culture, 2017)
Globalization has affected legal services and converged legal systems, especially in consumer protection in Indonesia and Australia. This process has resulted to a more formal, transparent, and adversarial laws and regulations that typically reflect to the common Law system. Then, the incorporation of local wisdom encourages significantly for the receptiveness of this globalization and convergence process both in Indonesia and Australia. This paper will show and analyze the extent to which globalization has affectedconsumer protection in Indonesia and Australia by dividing the impact from the result of economic liberalization and political fragmentation. It will then show how the incorporation of local wisdom canaccelerate the globalization of legal services and convergence of legal systems on consumer protection in Indonesia and Australia Keywords: Local Wisdom, Consumer Protection, Law, Indonesia, Australia.
Keywords: Globalization; Consumer Protection; Local Wisdom; Indonesia; Australia